Relationship among transactional and transformational leadership style, emotional intelligence and job performance of bank managers in Semnan Province, Iran - Shahhosseini, Mohammad (2012)
This study examined the relationship between emotional intelligence, leadership styles and Job performance. Data from 192 managers of banks indicated significant positive effects of emotional intelligence on job performance (r=.55, P<.001). In addition, it also appears that transformational leadership style is correlated with job performance (r=.45, P<.001), while transactional leadership is not correlated with the job performance (r=.076, P>.05). A factorial analysis of variance (ANOVA) was used to determine the influence of level of education, age, and management experience on job performance. The results of this research indicated that the level of education, age, and management experience had no significant effects on bank managers’ job performance. The findings of the study revealed that there is a significant difference in managers’ job performance in terms of type of bank (t=2.45,P<.05). The result of multiple regression about independent variables is that emotional intelligence and transformational leadership style altogether predict 35% of job performance. The study also showed that there is no significant difference in managers’ emotional intelligence and transformational/transactional leadership styles in terms of type of bank (t=.31, P>.05; =1.29,P>.05; and t=1.87,P>.05 respectively).